Challenges and opportunities for the Portuguese tuna pole-and-line supply chain from the Portuguese archipelagos of the Azores and Madeira - Priscila M. Silva; Cristina Pita; Cristina Pita; José L. Costa; Célia M. Teixeira (Frontiers in Sustainable Food Systems)
The tuna pole and line artisanal fleet in the Portuguese archipelagos of the Azores and Madeira depends entirely on these seasonal resources. Fishers and stakeholders were interviewed, and they have raised several concerns about the low economic value of the catch, the failure to meet market demand and the threats to the survival of the fleet. Fishers and stakeholders interviewed demonstrate a willingness to see an alternative management scheme that puts an end to the race to fish. Actions to address challenges related to catch quality, prices and market reputation were recommended to ultimately create more opportunities for the Portuguese tuna fleet.